2016
DOI: 10.1111/tme.12285
|View full text |Cite
|
Sign up to set email alerts
|

Blood donation in a large urban centre of southeast Brazil: a population‐based study

Abstract: This population-based study allowed us to characterise a high proportion of people that never reaches the blood centre. The results may be used to diversify the donor profile, creating strategies to target those least likely to donate blood, as women, white people and those with higher income and purchasing power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
8
2
2
Order By: Relevance
“…In our study, prior blood donation prevalence was lower than the 30% prevalence observed in other Brazilian studies among the general population in Florianópolis (Silva, Kupek, & Peres, 2013), Pelotas (Zago, Silveira, & Dumith, 2010), and Belo Horizonte (Moreno et al, 2016). We also found a higher prevalence of study participants who self-reported as being unable to donate blood; nearly 13% of the study participants compared to 3% among blood donor population in Belo Horizonte (Moreno et al, 2016). These discrepant results may be related to the source of study participants.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, prior blood donation prevalence was lower than the 30% prevalence observed in other Brazilian studies among the general population in Florianópolis (Silva, Kupek, & Peres, 2013), Pelotas (Zago, Silveira, & Dumith, 2010), and Belo Horizonte (Moreno et al, 2016). We also found a higher prevalence of study participants who self-reported as being unable to donate blood; nearly 13% of the study participants compared to 3% among blood donor population in Belo Horizonte (Moreno et al, 2016). These discrepant results may be related to the source of study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, blood donation was more frequent among males and higher socioeconomic and educational level, in line with other studies (Moreno et al, ; Silva et al, ; Zago et al, ). The association of blood donation and gender has already been described (Bilal et al, ; Gonçalez et al, ; Moreno et al, ). Lower rates of female donors were expected as on the global population, only 30% of blood donation is from females and, in some countries this rate is even lower, reaching only 10% (Bani & Giussani, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Blood banks around the world are struggling with a permanent deficit of blood and despite the efforts to understand the psychosocial factors associated with blood donation, little is known about the reasons for non‐donation and the impact of different barriers on blood donating behaviours in distinct populations . Recruiting and retaining safe blood donors are especially challenging in developing countries . In 2012, the whole blood donation rate for the country was 18·75 donations per 1000 inhabitants .…”
Section: Introductionmentioning
confidence: 99%
“…There was a considerable interest in Brazil for studying blood donor motivations, deterrents to donate and identifying population segments to be specifically targeted to improve blood donation (Zago et al, ; Gonçalez et al, ; Oliveira et al, ; Zangiacomi Martinez et al, ; Conceição et al, ; Moreno et al, ). This was well addressed by two studies from the same group supported by the US REDS programmes (Zago et al, ; Conceição et al, ).…”
Section: Resultsmentioning
confidence: 99%